Future Mathematics Teachers' Perceptions towards Inclusion in Secondary Education: University of Granada - Emilio Crisol-Moya; María Jesús Caurcel-Cara; Paula Peregrina-Nievas; Carmen del Pilar Gallardo-Montes (MDPI AG, 2023)
Designing and implementing inclusive practices is considered one of the basic actions for the construction of inclusive education. Actions depend largely on teachers' attitudes, which can be modified by the training they receive. This study analyzes 73 future mathematics teachers' perceptions of the diversity training received in the Master in Compulsory Secondary Education and Post-Secondary, Vocational Training and Language Teaching (MAES), as well as their attitudes towards diversity at the University of Granada (Spain). The participants' ages ranged from 22 to 50 years (M = 27.12, SD = 6.45); 47.9% were cisgender women and 52.1% were cisgender men. This research was a non-experimental, descriptive, and multivariate study, developed under the assumption of the quantitative methodological paradigm. The result revealed that attention to diversity should play an important role in the teachers' future teaching practice. Nevertheless, they were dissatisfied with the initial training received, considered themselves not qualified enough to face diversity in their classrooms, and they had an ambivalent attitude toward attention to diversity. However, attitudes and educational levels were more favorable in the case of women, older participants, and among those who had had contact with people with SNES. It is concluded that it is appropriate to continue to influence the attitudes in relation to this issue, since pedagogical training on the factors that condition the teaching-learning process in terms of attention to diversity provides greater effectiveness in this field.